Proyecto CORALBOT: una iniciativa para monitorear arrecifes de coral - Ordoñez Ávila, José Luis; Ordoñez Ávila, Marcial Gustavo; Perdomo, María Elena (Innovare: Revista de ciencia y tecnología, 2021)
The CORALBOT project was developed in 2019, as part of the Instituto Hondureño de Ciencia, Tecnología y la Innovación (IHCIETI) applied research projects. Images show the robot's first immersion in Punta Sal, Tela, Honduras, the final robot prototype and site´s coral reefs. In the future, the robot may be used to study ecosystems along the Honduran coastal shelf, as proposed by Alegría & Pérez, (2016).